2016
DOI: 10.3892/or.2016.5028
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-181d is a tumor suppressor in human esophageal squamous cell carcinoma inversely regulating Derlin-1

Abstract: Esophageal squamous cell carcinoma (ESCC) is the predominant subtype of human esophageal cancer in East Asia. In the present study, we explored the tumor suppressive function of microRNA-181d (miR-181d) in ESCC. Quantitative RT-PCR was used to assess gene levels of miR‑181d in both ESCC cell lines and clinical samples. Lentiviral transduction was used to overexpress miR-181d in ECA109 and Kyse30 cells. The possible tumor suppressive effects of miR-181d overexpression on ESCC proliferation, migration and cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Micro-RNA-181d functions as an important mediator in apoptosis, proliferation, and migration of AECs by targeting Bcl2 and Derlin1 (53,85). Increased expression of miRNA-181d in AECs exposed to CSE promotes cell apoptosis mainly through inhibiting the epithelial production of Bcl2, which is an antiapoptotic protein (44,71).…”
Section: Microrna-128b and Microrna-181dmentioning
confidence: 99%
“…Micro-RNA-181d functions as an important mediator in apoptosis, proliferation, and migration of AECs by targeting Bcl2 and Derlin1 (53,85). Increased expression of miRNA-181d in AECs exposed to CSE promotes cell apoptosis mainly through inhibiting the epithelial production of Bcl2, which is an antiapoptotic protein (44,71).…”
Section: Microrna-128b and Microrna-181dmentioning
confidence: 99%
“…Furthermore, miR-181d was found to mediate tumorigenesis and tumor development as a tumor suppressor. Ectopic expression of miR-181d suppressed cell proliferation and promoted apoptosis in osteosarcoma, colorectal cancer, gastric cancer, human esophageal squamous cell carcinoma and glioma (Wang et al, 2012;Li et al, 2016;Guo et al, 2017;Chen et al, 2018;Huang et al, 2018;Jiang et al, 2019). The expression levels of 76 miRNAs in the kidneys of mice with IRI were changed by at least two-fold, and the expression level of miR-181d was significantly decreased (Chen et al, 2004;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…DERL1 is a partner of the p97 ATPase complex and plays a key role in the mislocalization of the misfolded protein; it also integrates into the endoplasmic reticulum (ER) membrane to survey such protein aggregates [16, 17]. Recently, several studies have demonstrated that DERL1 contributes to carcinogenesis and tumor progression, and the upregulation of DERL1 expression promotes the development of colon cancer, esophageal cancer, and bladder cancer [18-20]. In addition, DERL1 is consistently overexpressed in NSCLC and correlated with tumor grade and lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%